2007
DOI: 10.1094/pdis-91-2-0164
|View full text |Cite
|
Sign up to set email alerts
|

Wheat streak mosaic virusin Australia: Relationship to Isolates from the Pacific Northwest of the USA and Its Dispersion Via Seed Transmission

Abstract: Wheat streak mosaic virus (WSMV) was found for the first time in Australia in 2002. It subsequently was found widely dispersed around the continent and was shown to be seedborne in wheat. The coat protein (CP) gene sequences of nine WSMV isolates from eastern and southwestern Australia are reported, one obtained directly from infected wheat seed, three from seedlings grown from infected wheat seed, and five from infected wheat plant samples. These sequences were compared with those of 66 WSMV CP sequences, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 19 publications
1
54
0
Order By: Relevance
“…Furthermore, absence of data does not demonstrate that this lineage was not present in other locations that could have served as a source. With respect to the second explanation, WSMV isolates from Australia are seed borne at 0.5-2% [2,11], a rate several log units greater than that previously reported for WSMV in maize [9]. However, as other Presented is a neighbor-joining tree based on 1,000 bootstrap iterations and rooted with the complete sequence of oat necrotic mottle virus (ONMV) designated as the outgroup.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, absence of data does not demonstrate that this lineage was not present in other locations that could have served as a source. With respect to the second explanation, WSMV isolates from Australia are seed borne at 0.5-2% [2,11], a rate several log units greater than that previously reported for WSMV in maize [9]. However, as other Presented is a neighbor-joining tree based on 1,000 bootstrap iterations and rooted with the complete sequence of oat necrotic mottle virus (ONMV) designated as the outgroup.…”
mentioning
confidence: 86%
“…Analysis of 3 0 -proximal partial nucleotide sequences [2] indicated that Australian isolates of WSMV were closely related to each other, and also to certain Clade D isolates from the American Pacific Northwest (APNW). As several of the Australian isolates are seed borne in wheat at low frequency [2,11], infected seed has been implicated as the means of initial introduction. Subsequent spread of WSMV within Australia was likely due to both seed transmission and vector transmission by the wheat curl mite [8].…”
mentioning
confidence: 99%
“…Molecular studies have enlarged the scope of plant virus epidemiology (17,21,31). Recently, renewed attention has been paid to ecological studies dealing with topics such as plant viruses in wild ecosystems, virus spread from wild to cultivated plants, virus emergence, and host plant domestication or movement (5,16,23,29,40). The resulting ecological and epidemiological scenarios are related to plant virus history or even prehistory.…”
Section: ϫ4mentioning
confidence: 99%
“…Symptom severity also depends on wheat cultivar, time of infection, temperature, and other environmental conditions that affect vector populations and plant growth [14]. Since its first discovery in 1922 in Nebraska, WSMV has periodically caused severe epidemics, across most of the Great Plains of the United States [3,8,15]. In the Texas Panhandle, much of the wheat is grown as a dual purpose crop, for both winter forage and grain production [10,12].…”
Section: Introductionmentioning
confidence: 99%